2012
DOI: 10.3109/13880209.2011.642886
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled essential oil fromChamaecyparis obtuseameliorates the impairments of cognitive function induced by injection of β-amyloid in rats

Abstract: EOCO suppressed both AD-related neuronal cell apoptosis and AD-related dysfunction of the memory system. Thus, the results of this study support EOCO as a candidate drug for the treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The passive avoidance test was performed as previously described, 36 with minor modifications. The rats were tested for memory retention deficits using a passive avoidance apparatus (Iwoo Scientific Co) consisting of a twocompartment dark/light shuttle box with a guillotine door separating the compartments.…”
Section: Passive Avoidance Testmentioning
confidence: 99%
“…The passive avoidance test was performed as previously described, 36 with minor modifications. The rats were tested for memory retention deficits using a passive avoidance apparatus (Iwoo Scientific Co) consisting of a twocompartment dark/light shuttle box with a guillotine door separating the compartments.…”
Section: Passive Avoidance Testmentioning
confidence: 99%
“…The following are only some recent examples of essential oils (EO) that have been shown to ameliorate pathological changes in in vivo animal models: Chamaecyparis formosensis Matsum . EO, Zataria multiflora Boiss . EO, Lavandula stoechas L. EO, Coriandrum sativum L. volatile oil or Juniperus communis L. oil .…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were verified by the observed inhibition of the superoxide dismutase activity, following treatment with essential oils [12]. The physiological effects of essential oils have contributed to alleviating the symptoms of various disorders, including allergies, multiple sclerosis, stroke, and cancer [13]. Furthermore, previous investigations have demonstrated that essential oils inhibit the enzymatic activities of cyclooxygenase and lipoxygenase, leading to the reduced production of eicosanoids [14].…”
Section: Introductionmentioning
confidence: 87%